1992
DOI: 10.1016/0378-1097(92)90327-k
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular degradation of poly(3-hydroxybutyrate) granules of Zoogloea ramigera I-16-M

Abstract: SUMMARYIntracellular degradation of poly(3-hydroxybutyrate) (PHB) in bacteria is not yet clear. The properties of the autodigestion of native PHB granules from Zoogloea ramigera 1-16-M were examined. The release of D( --)-3-hydroxybutyrate was observed only at pH values higher than about 8.5 and at relatively high ionic strength (optimal concentration 200 mM NaCI). Triton X-100 and diisopropylfluorophosphate inhibited this reaction. Addition of the supernatant fraction of Z. ramigera did not increase the relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
0
16
0
2
Order By: Relevance
“…The soluble intracellular PHB depolymerase from R. rubrum is active at pH 8.0 toward the native PHB granules from B. megaterium (16). The intracellular PHB depolymerase in soluble fractions from Z. ramigera I-16-M (18) and R. eutropha (21) also has a high optimum pH. PHB depolymerase characterized in this study was found only as a PHB granule-bound form.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The soluble intracellular PHB depolymerase from R. rubrum is active at pH 8.0 toward the native PHB granules from B. megaterium (16). The intracellular PHB depolymerase in soluble fractions from Z. ramigera I-16-M (18) and R. eutropha (21) also has a high optimum pH. PHB depolymerase characterized in this study was found only as a PHB granule-bound form.…”
Section: Discussionmentioning
confidence: 58%
“…In intracellular degradation of PHB in Ralstonia eutropha, weak hydrolysis activity against [ 14 C]PHB granules independent of the harvest time of the cells was reported (5). We have detected intracellular PHB depolymerase activity in Zoogloea ramigera I-16-M (18) and R. eutropha H16 (21), using proteasetreated native PHB granules as a substrate.…”
Section: Poly[d(ϫ)-3-hydroxybutyrate] (Phb) a Homopolymer Of D(ϫ)-3-mentioning
confidence: 99%
See 1 more Smart Citation
“…The methods for nPHB and dPHB granule preparation differ highly among PHA research laboratories: while Merrick et al and our laboratory isolated nPHB granules by glycerol density gradient centrifugation (32,34), others centrifuged crude cell extracts without glycerol and incubated the obtained polymer fraction with hydrolytic enzymes (25). The Saito laboratory used artificial PHB granules prepared according to the procedure described previously by Horowitz and Sanders (20) and used different surfactants such as oleate or phosphatidylglycerol in early investigations of intracellular PHB degradation (40,42,43). In recent studies, they used native PHB granules obtained by density gradient centrifugation (glycerol and sucrose) as the PHB depolymerase substrate (1,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the extracellular metabolism of PHB has been clarified in many bacteria and some fungi (6, 7). However, only a few studies on the intracellular degradation of PHB have been published (13,14,17,19,20). An intracellular PHB (iPHB) depolymerase system in Rhodospirillum rubrum was first reported in 1964 and consisted of a thermostable activator and a thermolabile esterase (13).…”
mentioning
confidence: 99%